Changes in active life expectancy among older thais: Results from the 1997 and 2004 National Health Examination Surveys - Uthaithip Jiawiwatkul (2018)
This study aims to determine the disability prevalence and changes in active life expectancy of the Thai older people between 1997 and 2004. Data on disability of older people aged ≥60 years were obtained from the National Health Examination Surveys. Disability refers to one or more restrictions on the activities of daily living. The Sullivan method was used to calculate active life expectancy. A total of 4048 older people in 1997 and 19 372 older people in 2004 were included in the analysis. Active life expectancy at age 60 of men was 16.5 years in 1997 and 17.6 years in 2004, whereas that of women was 17.9 and 19.9 years, respectively. Women spent a greater proportion of the remaining life with disability. The proportion of active life for both genders also increased during the 7-year period suggesting an evidence of the compression of morbidity in Thai older people. © 2012 APJPH.